#### Answer

$-\dfrac {8}{3}$

#### Work Step by Step

$5x-2\left( x+4\right) =3\left( 2x+1\right) \Rightarrow$
$ 5x-2x-8=6x+3\Rightarrow $
$3x-8=6x+3\Rightarrow 3x-6x=3+8\Rightarrow $
$-3x=8\Rightarrow x=-\dfrac {8}{3}$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$-\dfrac {8}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.